Morphological variability of the palmaris longus muscle in human fetuses - Olewnik, Łukasz (Surg Radiol Anat, 2018)
PURPOSE: The palmaris longus (PL) muscle is characterized by high-morphological variability. It is clinically important as it is routinely harvested for the reconstruction of other tendons. The study characterizes the morphology of the PL in human fetuses and creates a new classification based on its variations that would relate to the spectrum of morphological variability in adults. METHODS: Eighty spontaneously aborted human foetuses (44 male, 36 female, 160 upper limbs), aged 18–38 weeks of gestation, were examined. RESULTS: The palmaris longus muscle was present in 62.5% of fetuses. The absence was bilateral in 26.25%, and unilateral in 22.5%. Nine types of palmaris longus muscles were identified based on the morphology of its insertion (Types I–IX). All types originated on the medial epicondyle of the humerus. The most common type was Type I, which was characterized by insertion to the palmar aponeurosis (52%). The rarest types were Type VII and Type IX (1% each). Type VII was characterized by partial doubling of the muscle belly, which then turned into two separate tendons that inserted together into the palmar aponeurosis. Type IX was characterized by fusion with the flexor carpi ulnaris muscle. CONCLUSION: Our findings concerning morphological variability of the PL in fetuses present a new perspective on the understanding nature of the morphological variation of the PL muscle in adults. LIST OF EVIDENCE: Basic Science Study.